2022
DOI: 10.3389/fonc.2022.823831
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Mitochondria-Related Gene Signature to Predict the Prognosis in AML

Abstract: Mitochondria-related metabolic reprogramming plays a major role in the occurrence, development, drug resistance, and recurrence of acute myeloid leukemia (AML). However, the roles of mitochondria-related genes (MRGs) in the prognosis and immune microenvironment for AML patients remain largely unknown. In this study, by least absolute shrinkage and selection operator (LASSO) Cox regression analysis, 4 MRGs’ (HPDL, CPT1A, IDH3A, and ETFB) signature was established that demonstrated good robustness in TARGET AML … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…In addition, after dividing sepsis patients into two groups using consensus clustering, we observed the effect of MiRGs on the immune microenvironment of patients with Sepsis. The effect of MiRGs on immune infiltration in other diseases has been reported ( 41 43 ). We have observed that DE-MiRG screened in sepsis is associated with neutrophil immune infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, after dividing sepsis patients into two groups using consensus clustering, we observed the effect of MiRGs on the immune microenvironment of patients with Sepsis. The effect of MiRGs on immune infiltration in other diseases has been reported ( 41 43 ). We have observed that DE-MiRG screened in sepsis is associated with neutrophil immune infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…We then combined risk scores and clinical characteristics (age and gender) to develop a nomogram, indicating that risk score was an independent predictor. The predictive capability of our risk signature is equivalent to that of a signature including four genes ( 23 ) and a signature including six genes ( 22 ). However, our signature can better predict antitumor immune responses and promotes the finding of biological targets for immune treatments.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study didn’t explore the relationship of TME and metabolism. In addition, another study found that four mitochondria-related genes (HPDL, CPT1A, IDH3A, and ETFB) influence the prognosis and BM microenvironment of AML patients ( 23 ). However, the bioinformatics study was validated based on a children cohort and relatively simple: no omics integration analysis, no somatic mutation assessment, or without experimental validation.…”
Section: Introductionmentioning
confidence: 99%
“…Not only the gene expression patterns, imaging data, clinical characteristics [ 17 ], radiomics results [ 18 ], or other variables can also be used to establish prognostic models. Mitochondria play an important role in different cancers; mitochondria-related genes had also been used to build prognostic models of other diseases, for example, acute myeloid leukemia [ 19 ]. But this thinking perspective seems did not attract researchers' attention in previous breast cancer studies.…”
Section: Discussionmentioning
confidence: 99%